California Democratic Party Convention tentative agenda (1991)
This document is a tentative agenda update for the California Democratic Party Convention held in Oakland, March 1–3, 1991. It outlines Friday's schedule, including registration, credentials and rules committee meetings, numerous caucuses representing diverse constituencies (such as Chicano/Latino, Women's, African-American, Asian-Pacific, Environmental, Gay/Lesbian, Labor, and Young Democrats), and committee gatherings. The evening concludes with receptions, additional caucus meetings, and hospitality suites, reflecting broad participation across party groups.